Reading Attitudes And Habits Of Primary School English Language Teachers - Velusamy, Kanakambal (2018)
The main purpose of this study is to investigate the reading attitudes and habits of primary school English language teachers in Kinta District, Perak. The study is also aimed to find the selection of reading materials, the purpose of reading and the factors that hinder primary school English Language teachers from reading. The study also focused to suggest measures that are needed to improve the reading habits among these teachers. An explanatory mixed method design using questionnaires and interviews were applied to obtain information from 204 and 13 respondents respectively from English language primary school teachers in the Kinta District, Perak. The findings from the quantitative analysis revealed that teachers had an overall positive attitude towards reading (M=4.24, SD=.723) but only moderate level of reading habit (M=2.97, SD=1.844). Analysis of Variance (ANOVA) revealed no significant differences in reading attitude based on demographic variables: on gender and teachers’ qualifications. However, the results indicated significant differences between ethnicities, age groups and years of teaching experience. Results showed that the main purpose for teachers to read was for knowledge, examination or research purposes. The major factors hindering them from reading were cost factor and lack of self- motivation. However, in the qualitative findings, teachers revealed that they are aware of positive reading attitude and good reading habits are important to improve their proficiency level, build their confidence in the language and enhance their teaching practices. It also revealed that teachers were burdened with workload, thus hindering them from reading extensively.